Pilot Study of the Korean Parent Training Program Using a Partial Group‐Randomized Experimental Study. Issue 3 (19th March 2014) - Kim, Eunjung; Cain, Kevin; Boutain, Doris; Chun, Jin‐Joo; Kim, Sangho; Im, Hyesang
<x xml:space="preserve">Abstract</x> Problem Korean American (KA) parents need a culturally tailored parent training that helps them bridge the Korean and American cultures and divergent parenting practices. Methods The Korean Parent Training Program (KPTP) was pilot tested with 48 KA mothers of children between 3 and 8 years old using a partial group‐randomized controlled experimental study design. Researchers gathered self‐report survey and observation data. Findings Analyses, which used generalized estimating equations, indicated the intervention group mothers increased use of effective parenting practices and their children decreased behavioral problems and reported less acculturation conflict with their mothers. Conclusion The KPTP is a promising way to promote effective parenting and increase positive child mental health in KA families.